Aragonite–calcite veins of the 'Erzberg' iron ore deposit (Austria): Environmental implications from young fractures. Issue 2 (16th July 2018) - Boch, Ronny; Wang, Xianfeng; Kluge, Tobias; Leis, Albrecht; Lin, Ke; Pluch, Hannes; Mittermayr, Florian; Baldermann, Andre; Böttcher, Michael E.; Dietzel, Martin
Abstract: The well‐known Erzberg site represents the largest siderite (FeCO3 ) deposit in the world. It consists of various carbonates accounting for the formation of prominent CaCO3 (dominantly aragonite) precipitates filling vertical fractures of different width (centimetres to decimetres) and length (tens of metres). These commonly laminated precipitates are known as 'erzbergite'. This study focuses on the growth dynamics and environmental dependencies of these vein fillings. Samples recovered on‐site and from mineral collections were analyzed, and these analyses were further complemented by modern water analyses from different Erzberg sections. Isotopic signatures support meteoric water infiltration and sulphide oxidation as the principal hydrogeochemical mechanism of (Ca, Mg and Fe) carbonate host rock dissolution, mobilization and vein mineralization. Clumped isotope measurements revealed cool formation temperatures of ca 0 to 10°C for the aragonite, i.e. reflecting the elevated altitude Alpine setting, but unexpectedly low for aragonite nucleation. The 238 U– 234 U– 230 Th dating yielded ages from 285·1 ± 3·9 to 1·03 ± 0·04 kyrbp and all samples collected on‐site formed after the Last Glacial Maximum. The observed CaCO3 polymorphism is primarily controlled by the high aqueous Mg/Ca ratios resulting from dissolution of Mg‐rich host rocks, with Mg/Ca further evolving during prior CaCO3 precipitation and CO2 outgassing in the fissured aquifer. Aragonite represents the 'normal' mode of erzbergite formation and most of the calcite is of diagenetic (replacing aragonite) origin. The characteristic lamination (millimetre‐scale) is an original growth feature and mostly associated with the deposition of stained (Fe‐rich) detrital particle layers. Broader zonations (centimetre‐scale) are commonly of diagenetic origin. Petrographic observations and radiometric dating support an irregular nature for most of the layering. Open fractures resulting from fault tectonics or gravitational mass movements provide water flow routes and fresh chemical reaction surfaces of the host rock carbonates and accessory sulphides. If these prerequisites are considered, including the hydrogeochemical mechanism, modern water compositions, young U‐Th ages and calculated precipitation rates, it seems unlikely that the fractures had stayed open over extended time intervals. Therefore, it is most likely that they are geologically young.